Past and present in an alliance for the future - Darska, Bernadetta (Media - Culture - Social Communication, 2024)
Rec. Resilence Academic Team / Humanistyka prewencyjna, red. Ewa Domańska, Piotr Słodkowski, Monika Stobiecka, Wyd. Muzeum Sztuki Nowoczesnej w Warszawie, Poznańskie Centrum Dziedzictwa, Warszawa – Poznań 2022.